2013
DOI: 10.1146/annurev-biophys-083012-130417
|View full text |Cite
|
Sign up to set email alerts
|

Structural Biology of the Proteasome

Abstract: The proteasome refers to a collection of complexes centered on the 20S proteasome core particle, a complex of 28 subunits that houses proteolytic sites in its hollow interior. Proteasomes are found in eukaryotes, archaea, and some eubacteria, and their activity is critical for many cellular pathways. Important advances include inhibitor binding studies and the structure of the immunoproteasome, whose specificity is altered by incorporation of inducible catalytic subunits. The inherent repression of the 20S CP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
185
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(193 citation statements)
references
References 104 publications
2
185
0
2
Order By: Relevance
“…In eukaryotic cells, selective protein degradation is mostly carried out by a set of pathways of ubiquitylation that terminate in a 2.5-MDa protein proteolytic complex, called the 26S proteasome. The ubiquitin-proteasome pathways are essential parts of important biological processes, such as cell division, differentiation, innate immunity, adaptive immunity, regulation of gene expression, and the response to proteotoxic stress (1)(2)(3)(4). The proteasome is also an important therapeutic target in multiple myeloma (5,6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In eukaryotic cells, selective protein degradation is mostly carried out by a set of pathways of ubiquitylation that terminate in a 2.5-MDa protein proteolytic complex, called the 26S proteasome. The ubiquitin-proteasome pathways are essential parts of important biological processes, such as cell division, differentiation, innate immunity, adaptive immunity, regulation of gene expression, and the response to proteotoxic stress (1)(2)(3)(4). The proteasome is also an important therapeutic target in multiple myeloma (5,6).…”
mentioning
confidence: 99%
“…The intact proteasome has not been resolved to a level at which a reliable Cα-backbone can be traced with spatial assignment of amino acids, although major advances have been made in recent years (2,3,(7)(8)(9)(10)(11)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Several RP subunits have been resolved at high resolution by X-ray crystallography (14-16, 18, 21-24).…”
mentioning
confidence: 99%
“…The proteolytic activity of this multicatalytic protease resides inside the 20S core particle, built of four stacked rings of seven ␣ and ␤ subunits with ␣ 7 ␤ 7 ␤ 7 ␣ 7 organization. The internal cavity of the complex, defined by the two ␤ rings, encloses three pairs of distinct active sites named according to their differential cleavage site specificity: chymotrypsin-like (CT-L), 3 trypsin-like (T-L), and caspase-like (C-L) catalytic sites (1). Due to the closed conformation of the native 20S core complex, binding of different proteasome activators is required to induce opening of the 20S entry pores and allow injection of substrates into the catalytic chamber for degradation (2,3).…”
mentioning
confidence: 99%
“…The α 7 β 7 β 7 α 7 ring topology of the 20S enzyme ensures that the proteolytic active sites, which reside in the β-subunits, are sequestered and can only cleave substrates that enter the chamber through narrow axial pores formed by the α-subunits (3). As a consequence, ATP-dependent unfolding of natively folded protein substrates by the AAA+ ring and subsequent polypeptide translocation through a narrow axial channel and into the 20S chamber are required for degradation (4).…”
mentioning
confidence: 99%
“…It was proposed that as ATP hydrolysis progresses in the PAN and Rpt 1-6 rings, wobbling motions arise because the HbYX tails of newly ATP-bound subunits interact with binding pockets in the 20S α-subunit, whereas HbYX motifs in posthydrolytic subunits assume a nonbinding conformation (14). However, recent EM studies have shown that the rings of Rpt [1][2][3][4][5][6] and 20S shift into more symmetric and coaxially aligned positions upon substrate engagement, questioning the functional importance of dynamic wobbling (15).…”
mentioning
confidence: 99%